Prevention of Unwanted Pregnancy using Diethylstilbestrol in Mismated Bitches - Parmar, Bhanusinh M.; Panchal, Mahesh T.; Patel, Jagdish A.; Shukla, Tejas B. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Efficiency of diethylstilbestrol (DES) was evaluated for preventing unwanted pregnancy following misalliance in eight bitches of different breeds, age, and bodyweight along with use of vaginal cytology on the day of case registration for retrospective confirmation of stage of estrous cycle and time of mating. All the bitches were injected with diethylstilbestrol (DES) @ 2.0 mg/kg b. wt., i/m (Max. 20 mg) on day three and five post-mating and were subjected to blood examination on day zero and seven of DES injection. An ultra-sonographic scan was carried out in each of the bitch on day 30-35 post-mating to rule out the pregnancy status of the animal and success of therapy. All the bitches were followed up for 70-100 days post-treatment for any untoward effects. The major exfoliative cells found in vaginal cytology were of large intermediate/anuclear cells (94.37 ± 0.57 %) characteristics of a peak estrus phase, and 6 of 8 bitches also showed presence of sperm in the smear evinced mating. All the bitches were found to be non-pregnant on USG scan 30-35 days post-treatment and had no serious side effect during the follow-up period. The pre- and post-treatment mean values of hemoglobin (g/dL), WBCs (×103/μL) and RBCs (×106/μL) were 15.58 ± 0.59 vs. 15.33 ± 0.60, 9.10 ± 0.44 vs. 11.33 ± 1.60 and 6.94 ± 0.12 vs. 6.83 ± 0.22, respectively, differing non-significantly. It was concluded that the exfoliative vaginal cytology in bitches having fully cornified superficial/anuclear cells as predominant cells with sperm presence indicates misalliance during estrus phase. Injection diethylstilbestrol twice could prevent the conception and establishment of pregnancy in bitches having misalliance, with minimal effect on their health.